2010
DOI: 10.1093/jnci/djq458
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Cerebral Glioma Patients: A Systematic Review of Observational Studies

Abstract: In glioma, mild to moderate depressive symptoms may only rarely be due to tumor-associated structural or functional disruption of neuronal emotional networks. Improved methodological reporting would help clinicians better evaluate future studies, and facilitate improved evidence-based care of depressed glioma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(152 citation statements)
references
References 58 publications
6
143
3
Order By: Relevance
“…[20] Our rate of depression in patients with frontal tumours was similar to the overall patient-rated measures reported in the review by Rooney et al [20](i.e. 28.5% vs 27% respectively).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…[20] Our rate of depression in patients with frontal tumours was similar to the overall patient-rated measures reported in the review by Rooney et al [20](i.e. 28.5% vs 27% respectively).…”
Section: Discussionsupporting
confidence: 85%
“…Rooney et al [20]. For our non-frontal patients the mean score on the HADS depression subscale was lower than all but one of the studies reported by Rooney et al [20].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Most brain tumors present with specific neurologic signs due to mass effect, and 78% of patients with brain tumors had psychiatric symptoms, but only 18% presented only with these symptoms as the first clinical manifestation of a brain tumor 5 . Depression was found in 44% of all brain tumor patients, primary and metastatic 6 . We report a rare case associating delirium with the early presentation of brain metastization of melanoma.…”
Section: Dear Editormentioning
confidence: 99%
“…Depression was associated with a decline in physical function, cognitive deficit, and quality of life among brain tumor patients 14 . In addition, patients with glioma are at higher risk of phychiatric disorders during the period of diagnosis 15,16 .…”
mentioning
confidence: 97%